The Relationship of Pre-operative Knowledge Levels with Anxiety Levels in Pre-Cataract Surgery Clients - Setyawan, Bambang; Windarwati, Heni Dwi; Nova, Renny (Promotion and Prevention in Mental Health Journal, 2021)
Cataract is one of the eye diseases that causes the most blindness in Indonesia. Various factors influence the patient's attitude towards cataract surgery, such as education and knowledge. One's knowledge will be able to reduce feelings of anxiety in perceiving something. The purpose of this study is to analyze the relationship between the level of knowledge about pre-cataract surgery with the anxiety level of pre-cataract clients at RSUD Dr. Saiful Anwar Malang. This study used a quantitative method with a cross-sectional research design with total sampling and a questionnaire about pre-cataract surgery clients' knowledge and anxiety levels using the non-probability sampling method. The total number of respondents is 60 clients. The results showed that 34 respondents had a low level of knowledge (66.67%). A total of 21 (41.18%) respondents experienced moderate anxiety. The Chi-Square test results showed a difference in a p-value of 0.040 (α < 5%), which showed a close relationship between the level of knowledge and anxiety in pre-cataract surgery clients at Dr. Saiful Anwar Hospital Malang. Most pre-cataract surgery patients have a low level of knowledge and experience moderate anxiety. So, there is a relationship between the patient's level of knowledge and anxiety before cataract surgery. The lower the level of knowledge, the higher the anxiety experienced by the patient